2018
DOI: 10.1097/pp9.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and the Development of Substance Use Disorders: Current Knowledge and Future Directions

Abstract: Physical activity and exercise are positive health behaviors that have been shown to reduce the risk of physical and psychological diseases. There is a strong rationale that physical activity could be a protective factor against the development of substance use disorders (SUDs), which include some of the most common mental health conditions such as tobacco and alcohol use disorder. This review examined the epidemiological literature to describe the associations of physical activity and substance use across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 64 publications
2
26
1
Order By: Relevance
“…Whereas among girls, adherence to the physical activity recommendation only or all three recommendations was associated with lower odds of cannabis use. Our results are somewhat consistent with previous studies indicating a negative association between physical activity and cannabis use [ 15 ]. For example, Wichstrøm and Wichstrøm [ 71 ] found that participation in team sports and endurance sports may reduce later cannabis use.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Whereas among girls, adherence to the physical activity recommendation only or all three recommendations was associated with lower odds of cannabis use. Our results are somewhat consistent with previous studies indicating a negative association between physical activity and cannabis use [ 15 ]. For example, Wichstrøm and Wichstrøm [ 71 ] found that participation in team sports and endurance sports may reduce later cannabis use.…”
Section: Discussionsupporting
confidence: 93%
“…This is the first study to examine the association between all possible combinations of screen time, sleep duration, and physical activity with substance use among adolescents. Past research has mainly focused on investigating the associations between a single recommendation of the guidelines and substance use among adolescents [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 32 ], ignoring how these behaviors may concurrently relate to substance use among adolescents. We observed that different combinations of the guideline recommendations were associated with all substance use differentially between type of recommendation met, type of substance use, and gender, as well as age for cannabis use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Torstveit and al, which included more than 3200 junior-high and high-school students in southern Norway, found that organized sport participation was consistently associated with decreased odds of unhealthy lifestyle habits, including cannabis misuse [47]. Brellenthin et al reviewed the epidemiological literature to describe the associations of physical activity and substance misuse across the lifespan and concluded that physical activity is negatively associated with drug use [48]. With regard to cannabis consumption, some studies reported no relationship and some reported positive associations (i.e., protective effect of sport); however, in other studies, authors highlighted negative associations between sports participation and marijuana use [19,49,50].…”
Section: Discussionmentioning
confidence: 99%